Changes in the Politico-Geographical Position of Hungary in the 20th Century - Hajdú, Zoltán (Discussion Papers, 1998)
The political geographical and geopolitical situation of Hungary has constantly changed throughout history, however, significant changes having a powerful impact on current processes have only taken place in the 20th century. The Austrian-Hungarian Monarchy collapsed as a formal great power and a functional middle power, and its former component, Hungary, has become a small state. Hungary did not lose significant territories after the 2nd World War, the fundamental change was brought about by the Soviet occupation and the forced integration into the Soviet system of power. Following the collapse of the bipolar world system, the country has changed its orientation embarking on the road towards the European Union and the NATO. No longer being the “West of the East”, it has gradually become the “East of the West”.